Multidisciplinary non-pharmacological treatments with effects on pain modulation and functioning in spondyloarthropathies – a systematic review - Adelina Elena Ungureanu; Liliana-Elena Stanciu; Andreea-Bianca Uzun; Emma Gheorghe; Loredana Pazara; Steliana-Roxana Miclaus; Viorela-Mihaela Ciortea; Andra-Iulia Suceveanu; Madalina Gabriela Iliescu (Balneo and PRM Research Journal, 2023)
Treatment for chronic rheumatic diseases, included various modalities for pain management and for functioning modulation, has the main gole to increase the quality of life and to improve also the activities of daily living. Seronegative spondyloarthropathies (SpA) are a group of rheuma-tologic disorders that include ankylosing spondylitis, psoriatic arthritis, entheropatic SpA, reac-tive arthritis and undifferentiated SpA. Treatment methods include clasically pharmacological modalities. Physical therapy should also be highlighted as being part of the treatment. Balneo-therapy and spa therapy are increasingly taken into account in evidence-based treatment guide-lines for multiple rheumatic diseases, for specific effects on functional parameters and also for the involvement in cartilage regeneration. Balneotherapy is universally defined as the treatment method which uses bathing in thermal and mineral waters. Other balneological treatments in-clude peloidotherapy, balneological gases and therapeutic waters in various forms of bathing, inhalation or drinking. Spa therapy comprises complementary and alternative treatment modal-ities including balneotherapy, hydrotherapy, exercises, and massage therapy. This systematic literature review aims to highlight the effects of balneotherapy in spondylarthropathies. The review is based on the internationally accepted method, the “PRISMA” methodology- “Pre-ferred Reporting Items for Systematic Reviews and Meta-Analysis”.